The Relationship Between Body Mass Index and Inflammatory Parameters in HIV Patients Treated with Antiretrovirals - Theresia, Lydia; Lindarto, Dharma; Syafril, Santi; Kembaren, Tambar (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Antiretroviral administration affects weight gain and inflammation in HIV patients. The purpose of the study was to assess the relationship of body mass index with inflamation parameters in HIV patients who ARV therapy. In 40 HIV patients (stage III-IV)Â Â treated with ARV (FDC 87%, Durival Efaviren 7.5%, Tenofovir, Huviral, Aluvia 2.5%, and Tenofovir, Huviral, Neviral 2.5%) conducted observational analytics with crosssectional design. CD4 examination was carried out flowcytometrically, BMI measured by formula weight (kg) divided by height squared (m2), waist circumference (WC) measured by ribbon between costae arcus and anterior superior iliac spine, albumin measurement with Brom Cresol Green (BCG) method. There is a significant correlation between BMI with WC and CD4 (r=0.61, p<0.001 and r=0.38, p<0.001, respectively). There is no correlation between BMI and duration of ARV treatment, albumin and leptin. ARV treatment in HIV patients will affect weight and inflammatory markers.